Isolation, characterization, and comparison of nanocrystalline cellulose from solid wastes of horse chestnut and chestnut seed shell - Ozkan, Betul Cicek; Guner, Melek (Springer, 2022)
The horse chestnut seed shell (HC) and chestnut seed shell (CT) were evaluated as renewable, sustainable, and cheap raw materials transformed into valuable products, cellulose nanocrystals (CNCs). Alkali and bleaching treatments were performed to obtain horse chestnut cellulose (HCS) and chestnut cellulose (CTS) and subsequently isolated to the horse chestnut cellulose nanocrystal (HC-CNC) and chestnut cellulose nanocrystal (CT-CNC) by sulphuric acid hydrolysis. Raw materials and their products were comparatively investigated at each stage of the isolation process. The cellulose, hemicellulose, and lignin content of HC and CT were determined via chemical composition analysis. The structural analysis was performed using Fourier transform infrared spectroscopy and X-ray diffraction technics for CNCs. Morphological analysis and size range determination of the samples were carried out via atomic force microscopy (AFM) and particle size analysis. Zeta potential and particle size distribution were determined by analyzing the surface and particle size. The thermal behaviors were investigated at different phases of treatments using thermal gravimetric analysis (TGA/DTG). HC-CNC demonstrates a higher crystallinity index value of 85.49% and a lower yield of 20.46%, whereas CT-CNC shows a lower crystallinity of 65.06% and a higher yield of 36.59%. A differentiation in structural, thermal, and morphological properties of extracted celluloses and isolated CNCs was observed depending on the source of the raw materials. However, a morphological alteration in CNC structures has emerged relative to precursor cellulose after the acid hydrolysis process as an essential finding via AFM studies. The solid wastes horse chestnut and chestnut seed shells offer great potential as suitable, sustainable, and environmentally friendly starting raw materials to produce CNC and in applications, including wastewater treatments, biosensing, wound dressing, and reinforcement for polymer composites due to their excellent thermal and structural properties.
Keywords: Cellulose nanocrystal; Horse chestnut; Chestnut; Extraction; Characterization; Solid waste